Experimental Study of Cationic-Modified Biopolymer for Increasing the Shear Strength of Sand - Ardiana, Andra; Lim, Aswin; Muljana, Henky (Jurnal Teknik Sipil dan Perencanaan, 2024)
The application of biopolymers as a more environmentally friendly alternative to cement has emerged as an interesting research subject.The purpose is to enhance the shear strength of sandy soils. In this article, the selected biopolymer is cationic-modified starch. It is expected that cationic starch will have less water absorption properties since modified starch has cationic groups in place of the OH- groups found in the normal starch. This cationic-modified starch namely Amylofax. Five types of samples are created for this testing, including Sample A is prepared with the composition of  (silica sand + 2% Amylofax T1100 (w/w) + 20% water (w/w))., Sample B consists of (silica sand + 2% Amylofax T2200 (w/w) + 20% water (w/w))., Sample C is comprised of (silica sand + 2% Amylofax T1100 (w/w) + 2% Glucomannan (w/w) + 20% water (w/w)), Sample D consists of (silica sand + 2% Amylofax T2200 (w/w) + 2% Glucomannan (w/w) + 20% water (w/w)), and Sample E includes (Ottawa sand + 2% cement (w/w) + 20% water (w/w)). The samples were tested using a direct shear test apparatus to determine the soil shear strength parameters (c) cohesion and (Ø) internal friction angle. After conducting the tests on the sand samples with the addition of modified starch biopolymer (cationic starch), it was found that the cohesion value was 961kPa, and the internal friction angle was 63°. These results indicate higher shear strength values compared to sand mixed with natural starch.